The functional consequences of social attention on memory precision and on memory-guided orienting in development. (April 2019) - Doherty, Brianna Ruth; Fraser, Alexander; Nobre, Anna Christina; Scerif, Gaia
Abstract: Adults are slower at locating targets in naturalistic scenes containing a social distractor compared to an equally salient non-social distractor, and their subsequent memory for targets in social scenes is poorer. Therefore, adults' social biases affect not only attention, but also their memory. Six-to-ten year-old children and young adults took part in the current study, employing a combination of behavioural and eye-tracking measures. Social stimuli in naturalistic scenes distracted both children and adults during visual search, as demonstrated by their gaze behavior and search times. In addition, eye-tracking revealed even greater attentional capture by social distractors for children. Memory for targets was worse in social compared to non-social scenes. Intriguingly, children demonstrated overall better memory precision than adults. Finally, when participants detected previously learnt targets within visual scenes, adults were slower for targets appearing at unexpected (invalid) locations within social scenes compared to non-social scenes, but this was not the case for children. In their entirety, these findings suggest that the interplay between social attentional biases, memory and memory-guided attention is complex and modulated by age-related differences. Complementary methodologies in developmental cognitive neuroscience shed light on the mechanisms through which social attention and memory interact over development.